2013
DOI: 10.1007/s11144-013-0552-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of the surface evolution of nitrogen species on CuO/CeZrO2 catalysts

Abstract: A series of CuO/CZ catalysts with different amounts of copper oxide were synthesized from copper nitrates by incipient wetness impregnation of the ceria-zirconia support. The structural, redox, acidic and adsorption properties were investigated using X-ray diffraction (XRD), BET, H 2 temperature programmed reduction (H 2 -TPR), temperature programmed desorption of NO in the presence of oxygen (NO-TPD) and in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). The results have shown good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…It is known that NO 2 as a powerful oxidant can greatly promote the soot oxidation process. The NO 2 production capacity is affected by the oxidation of gaseous NO and the decomposition capacity of the nitrates stored at low temperatures. Figure a shows the NO 2 production profiles of the FeCeO 2−δ and BaFeCeO 2−δ catalysts obtained in the NO-TPO experiments. To analyze the effect of the barium loading on the NO oxidation to NO 2 , we compared the catalyst samples with different barium contents.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that NO 2 as a powerful oxidant can greatly promote the soot oxidation process. The NO 2 production capacity is affected by the oxidation of gaseous NO and the decomposition capacity of the nitrates stored at low temperatures. Figure a shows the NO 2 production profiles of the FeCeO 2−δ and BaFeCeO 2−δ catalysts obtained in the NO-TPO experiments. To analyze the effect of the barium loading on the NO oxidation to NO 2 , we compared the catalyst samples with different barium contents.…”
Section: Resultsmentioning
confidence: 99%
“…Our interest in this study is on CuO, a p-type semiconducting material, which has been reported for detection of NO x [9][10][11][12][13][14], CO [12,[15][16][17], H 2 [18][19][20], and ethanol [14,[20][21][22][23][24][25]. CuO has also been studied as a NO x reduction catalyst in SCR [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it can be found from the figure that the M-Ce80Zr20 support showed a broad peak at a higher temperature (620 • C), which can be attributed to the reduction of the surface Ce 4+ . It has been reported that the reduction temperature of CuO species should be lower than that of the free CuO when supported on fluorite-type oxides [34]. Therefore, the reduction peak in the range of 197-323 • C could be ascribed to the reduction of the CuO species, which had a closely synergistic effect on the M-Ce80Zr20 supports.…”
Section: H 2 -Tpr Analysismentioning
confidence: 94%